L1 USED DURING L2 FREE WRITING: A LOOK AT BEGINNING WRITERS - Indah Nur 'Aini (Journal of English Language Teaching and English Linguistics, 2015)
This research aims to investigate the composing process and writing strategiesofthe beginning writers’free writing product dealing with the writing problem and theory of the writing process. It is seenfrom their grammar (minor grammatical errors, such as –s on verbs in third person singular),vocabulary (knows most words needed to express ideas but lacks vocabulary for finer shades ofmeaning), sentence (uses several sentences pattern), organization (somewhat sequenced), and fluency(writes several sentences). It focuses on how the beginning writers’ L1 influence their L2 free writingproduct. Twenty five (25) students invoked by producing twenty five (25) different topics. The resultshows that there is an influence of L1 knowledge to L2 language production in which the participantstranslate their ideas in L1 knowledge to L2 language directly without considering the structures andforms.